The duration of intervals on the oral cancer care pathway and implications for survival: a systematic review and meta-analysis - Nicolás Francisco Fernández-Martínez; Nicolás Francisco Fernández-Martínez; Nicolás Francisco Fernández-Martínez; Dafina Petrova; Dafina Petrova; Dafina Petrova; Zuzana Špacírová; Zuzana Špacírová; Zuzana Špacírová; Rocío Barrios-Rodríguez; Rocío Barrios-Rodríguez; Rocío Barrios-Rodríguez; et al. (Frontiers Media S.A., 2023)
IntroductionPrevious studies measuring intervals on the oral cancer care pathway have been heterogenous, showing mixed results with regard to patient outcomes. The aims of this research were (1) to calculate pooled meta-analytic estimates for the duration of the patient, diagnostic and treatment intervals in oral cancer, considering the income level of the country, and (2) to review the evidence on the relationship of these three intervals with tumor stage at diagnosis and survival.Materials and methodsWe conducted a systematic review with meta-analysis following PRISMA 2020 guidelines (pre-registered protocol CRD42020200752). Following the Aarhus statement, studies were eligible if they reported data on the length of the patient (first symptom to first presentation to a healthcare professional), diagnostic (first presentation to diagnosis), or treatment (diagnosis to start of treatment) intervals in adult patients diagnosed with primary oral cancer. The risk of bias was assessed with the Aarhus checklist.ResultsTwenty-eight studies reporting on 30,845 patients met the inclusion criteria. The pooled median duration of the patient interval was 47 days (95% CI = 31-73), k = 18, of the diagnosis interval 35 days (95% CI = 21-38), k = 11, and of the treatment interval 30 days (95% CI = 23-53), k = 19. In lower-income countries, the patient and treatment intervals were significantly longer, and longer patient intervals were related to later stage at diagnosis. In studies with a lower risk of bias from high-income countries, longer treatment intervals were associated with lower survival rates.ConclusionInterval duration on the oral cancer care pathway is influenced by the socio-economic context and may have implications for patient outcomes.